N-terminal domain of ARF-GEF GNOM prevents heterodimerization with functionally divergent GNL1 in Arabidopsis - Brumm, Sabine; Singh, Manoj K.; Kriechbaum, Choy; Richter, Sandra; Huhn, Kerstin; Kucera, Tim; Baumann, Sarah; Wolters, Hanno; Takada, Shinobu; Juergens, Gerd (Plant Journal, 2022)
Evolutionary change following gene duplication can lead to functionally divergent paralogous proteins. If comprising identical subunits their random assortment would also form potentially detrimental heteromeric proteins. In Arabidopsis, the ARF GTPase guanine-nucleotide exchange factor GNOM is essential for polar recycling of auxin-efflux transporter PIN1 from endosomes to the basal plasma membrane whereas its paralog GNL1 mediates retrograde Golgi-endoplasmic reticulum traffic. Here we show that both GNOM and GNL1 form homodimers but no heterodimers. To assess the biological significance of this, we generated transgenic plants expressing engineered heterodimer-compatible GNOM variants. Those plants showed developmental defects such as the failure to produce lateral roots. To identify mechanisms underlying heterodimer prevention, we analyzed interactions of the N-terminal dimerization and cyclophilin-binding (DCB) domain. Each DCB domain interacted with the complementary fragment (ΔDCB) both of their own and of the paralogous protein. However, only DCBGNOM interacted with itself whereas DCBGNL1 failed to interact with itself and with DCBGNOM. GNOM variants in which the DCB domain was removed or replaced by DCBGNL1 revealed a role for DCB-DCB interaction in the prevention of GNOM-GNL1 heterodimers whereas DCB-ΔDCB interaction was essential for dimer formation and GNOM function. Our data suggest a model of early DCB-DCB interaction that facilitates GNOM homodimer formation, indirectly precluding formation of detrimental heterodimers.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Arabidopsis; ARF-GEF paralogs; DCB domain; domain interaction; heterodimer prevention; homodimers